2003
DOI: 10.1136/mp.56.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori on apoptosis and apoptosis related genes in gastric cancer cells

Abstract: Background/Aims: Helicobacter pylori induces the apoptosis of gastric epithelial cells in vivo and in vitro. However, the molecular mechanism has not been clarified. The aim of this study was to investigate the effect of H pylori on the apoptosis of gastric epithelial cells and the expression of apoptosis related genes in vitro. Methods: Human gastric adenocarcinoma SGC-7901 cells were co-cultured with a cytotoxic H pylori strain, NCTC 11637, at various densities ranging from 3.2 × 10 4 to 1.0 × 10 8 colony fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 30 publications
5
34
0
Order By: Relevance
“…On the other hand, Bax was detected in all groups with the highest expression in the group with H pylori infection alone, which also presented Bcl-2 expression as mentioned above. Although some authors have shown an increased Bcl-2 expression in H pylori-positive cases, in the group (Hp+/EBV-) the Bcl-2 expression was very low [33][34][35][36][37] . Although it was not statistically significant, our findings suggest a possible correlation between H pylori and Bcl-2 expression, unlike with EBV.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Bax was detected in all groups with the highest expression in the group with H pylori infection alone, which also presented Bcl-2 expression as mentioned above. Although some authors have shown an increased Bcl-2 expression in H pylori-positive cases, in the group (Hp+/EBV-) the Bcl-2 expression was very low [33][34][35][36][37] . Although it was not statistically significant, our findings suggest a possible correlation between H pylori and Bcl-2 expression, unlike with EBV.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [66] described that H pylori induces apoptosis in human gastric adenocarcinoma cells mediated by an increased expression of MYC mRNA.…”
Section: Myc and Gastric Carcinogenesismentioning
confidence: 99%
“…Fas-mediated apoptosis in gastric cells was also described upon infection by H. pylori, however in this case other apoptotic factors are involved as well. These include TRIAL and its receptor subtypes (Yang, et al 2003;Martin et al, 2004). Because the binding of Fas ligand (FasL) to the Fas antigen results in the transduction of a cytolytic signal into the cell followed by apoptosis, cells overexpressing GKN1 showed an increase in apoptosis that is mainly due to the exposure of the MKN28 cells to FasL with respect to that observed in the absence of FasL.…”
Section: Evaluation Of Transient Expression Of Gkn1 In Gastric Cancermentioning
confidence: 98%